The Marginal Fitness of CAD/CAM All Ceramic Crowns Constructed by Two Typesof Direct Digitization Techniques (An In Vitro Study) - Khdeir, Rana M; Ibraheem, Adel F (Journal of Baghdad College of Dentistry, 2016)
Background: In capturing a negative image, the digital impression secures a digital record for the purposeof designing and creating restorations. The introduction of scanning system presents a paradigm shift in the way of the dental impression procedure and encourages the accuracy of obtained restoration especially in the marginal area as a result of producing accurate final impression The digital system offers many advantages over the Conventional method.. The objective of this present in vitro study was to evaluate the marginal fitness of all ceramic crowns fabricated by direct digital scanning of the prepared tooth using two types of intra-oral cameras (Bluecam camera with strip light projection technique and Omnicam camera with video sampling technique). Materials and Methods: Sixteen sound upper first premolar teeth of comparable size were collected. Standardized preparation of all teeth samples were carried out to receive all ceramic crown restoration with deep chamfer finishing line (1mm), axial length (4mm) and convergence angle (6â—¦). The specimens divided in to two groups according to the type of digital impression technique: Group A, eight prepared teeth scanned directly by Bluecam camera; Group B, eight prepared teeth scanned directly by Omnicam camera. Then CAD/CAM all ceramic crowns constructed for each tooth sample. Marginal discrepancy was measured at Sixteen points per tooth using digital microscope at (120X) magnification. Results: Independent sample t-test was used to identify and localize the source of difference among the groups. It was found that there is statistically non- significant difference in the marginal gap mean values between (group A and group B). Conclusions: From the above result we can conclude that the two types of direct digitization techniques have the same accuracy.